High-Mobility n‑Type Conjugated Polymers Based on Electron-Deficient Tetraazabenzodifluoranthene Diimide for Organic Electronics - Li, Haiyan; Kim, Felix Sunjoo; Ren, Guoqiang; Jenekhe, Samson A (Journal of the American Chemical Society, 2013)
High-mobility p-type and ambipolar conjugated polymers have been widely reported. However, high-mobility n-type conjugated polymers are still rare. Herein we present poly(tetraazabenzodifluoranthene diimide)s, PBFI-T and PBFI-BT, which exhibit a novel two-dimensional (2D) π-conjugation along the main chain and in the lateral direction, leading to high-mobility unipolar n-channel transport in field-effect transistors. The n-type polymers exhibit electron mobilities of up to 0.30 cm2/(V s), which is among the highest values for unipolar n-type conjugated polymers. Complementary inverters incorporating n-channel PBFI-T transistors produced nearly perfect switching characteristics with a high gain of 107.